IMPACT OF AIR POLLUTANTS ON CHILDREN'S RESPIRATORY HEALTH (CASE STUDY: INDUSTRIAL AREA) - Amirah, Nada; Azhary, Muhammad Rifqi; Putri, Sindy Yulia (Fakultas Ilmu Kesehatan, Universitas Ibn Khaldun, Bogor, 2025)
The fifth biggest cause of death globally due to respiratory and cardiovascular diseases, air pollution has been steadily increasing over the last several years. This article's goal is to provide a synopsis of a number of pertinent studies that discuss the concentration of pollutants caused by industrial emissions, the impact of being close to the industry, and the consequences of these variables on respiratory health. A systematic review approach is used in this piece. Three scientific databases—ProQuest, PubMed, and ScienceDirect—conducted a literature search for articles published during the last decade. Study participants had to be either children or teenagers, there had to be at least one site in an industrial region, the study had to deal with respiratory symptoms, respiratory illness, and/or pulmonary function testing. Only seven papers out of two hundred and twenty-two were ultimately considered for inclusion in the systematic review. Both pollution concentrations and children's respiratory difficulties are shown to be greater in locations close to industries as opposed to places further away, according to the included publications.